2017
DOI: 10.1088/1361-6560/aa8d09
|View full text |Cite
|
Sign up to set email alerts
|

Deep convolutional neural network with transfer learning for rectum toxicity prediction in cervical cancer radiotherapy: a feasibility study

Abstract: Better understanding of the dose-toxicity relationship is critical for safe dose escalation to improve local control in late-stage cervical cancer radiotherapy. In this study, we introduced a convolutional neural network (CNN) model to analyze rectum dose distribution and predict rectum toxicity. Forty-two cervical cancer patients treated with combined external beam radiotherapy (EBRT) and brachytherapy (BT) were retrospectively collected, including twelve toxicity patients and thirty non-toxicity patients. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
138
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(139 citation statements)
references
References 67 publications
1
138
0
Order By: Relevance
“…This approach has been successfully applied to medical image segmentation problems by transferring knowledge from natural image applications (e.g., Google ImageNet database) 70 . This idea can be extended to other tasks, where Zhen et al demonstrated a CNN for predicting rectal toxicity in cervical cancer radiotherapy by fine‐tuning a pretrained network (VGG‐16) on the natural images from ImageNet 71 …”
Section: What Data Are Needed For Ml/dl Applications?mentioning
confidence: 99%
“…This approach has been successfully applied to medical image segmentation problems by transferring knowledge from natural image applications (e.g., Google ImageNet database) 70 . This idea can be extended to other tasks, where Zhen et al demonstrated a CNN for predicting rectal toxicity in cervical cancer radiotherapy by fine‐tuning a pretrained network (VGG‐16) on the natural images from ImageNet 71 …”
Section: What Data Are Needed For Ml/dl Applications?mentioning
confidence: 99%
“…This rapid development is partly stimulated by its many important applications, one of which is drug toxicity prediction in silico [88,127,158]. Together with “Big Data” science [159], machine learning techniques may provide much more information about toxicity than ever before.…”
Section: Discussionmentioning
confidence: 99%
“…Many research scientists [89][90][91][92][93][94][95] have investigated the application of ML in radiotherapy treatment response and outcome predictions. Lee et al [89] studied utilizing of Bayesian network ensemble to predict radiation pneumonitis risk for NSCLC patients whom received curative 3D conformal radiotherapy.…”
Section: Treatment Outcomementioning
confidence: 99%
“…Their findings indicated that prediction of treatment response can be improved by utilizing data mining approaches, which were able to unravel important non-linear complex interactions among model variables and have the capacity to predict on unseen data for prospective clinical applications. Zhen et al [91] introduced a CNN model to analyze the rectum dose distribution and predict rectum toxicity. The evaluation results demonstrated the feasibility of building a CNN-based rectum dose-toxicity prediction model with transfer learning for cervical cancer radiotherapy.…”
Section: Treatment Outcomementioning
confidence: 99%